2005
DOI: 10.1073/pnas.0505164102
|View full text |Cite
|
Sign up to set email alerts
|

Growth-associated protein GAP-43 and L1 act synergistically to promote regenerative growth of Purkinje cell axons in vivo

Abstract: Neuronal expression of growth-associated protein 43 (GAP-43) and the cell adhesion molecule L1 has been correlated with CNS axonal growth and regeneration, but it is not known whether expression of these molecules is necessary for axonal regeneration to occur. We have taken advantage of the fact that Purkinje cells do not express GAP-43 or L1 in adult mammals or regenerate axons into peripheral nerve grafts to test the importance of these molecules for axonal regeneration in vivo. Transgenic mice were generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 45 publications
0
71
0
Order By: Relevance
“…Although the addition of L1 by soluble, viral, or genetic means produces conflicting evidence that L1 either can enhance or inhibit axonal outgrowth (Kobayashi et al, 1995;Webb et al, 2001;Adcock et al, 2004;Zhang et al, 2005;Chen et al, 2007), results from the adult L1 mutant model provide clear-cut negative evidence that L1 is not required for C-fiber primary afferents (present study) or corticospinal tract axons (Jakeman et al, 2006) to sprout. Furthermore, we can conclude from the present data that the absence of L1 does not permit enhanced outgrowth of peptidergic sensory neurons after an injury.…”
Section: L1 Is Not Required For Cgrp-positive Afferent Sproutingmentioning
confidence: 65%
See 1 more Smart Citation
“…Although the addition of L1 by soluble, viral, or genetic means produces conflicting evidence that L1 either can enhance or inhibit axonal outgrowth (Kobayashi et al, 1995;Webb et al, 2001;Adcock et al, 2004;Zhang et al, 2005;Chen et al, 2007), results from the adult L1 mutant model provide clear-cut negative evidence that L1 is not required for C-fiber primary afferents (present study) or corticospinal tract axons (Jakeman et al, 2006) to sprout. Furthermore, we can conclude from the present data that the absence of L1 does not permit enhanced outgrowth of peptidergic sensory neurons after an injury.…”
Section: L1 Is Not Required For Cgrp-positive Afferent Sproutingmentioning
confidence: 65%
“…If L1 has a role in CGRP-positive afferent sprouting after injury, the present results indicate that alternate factors must compensate for its absence (Adcock et al, 2004;Jakeman et al, 2006). Although L1 promotes axonal outgrowth in some models (Kobayashi et al, 1995;Webb et al, 2001;Adcock et al, 2004;Zhang et al, 2005;Chen et al, 2007), it also can have inhibitory effects depending on its binding partners (for review see Kamiguchi and Lemmon, 1997;Castellani et al, 2000). For example, Chaudhry et al (2006) found that co-expression of L1 with nerve growth factor reduced CGRP-positive sprouting within the spinal cord, and that this reduction did not occur with other cell adhesion molecules.…”
Section: L1 Is Not Required For Cgrp-positive Afferent Sproutingmentioning
confidence: 68%
“…it is downregulated on myelinated axons and re-expressed in regenerating axons after spinal cord injury [64,65] . Exogenous L1CAM is beneficial in promoting axon growth and functional recovery after spinal cord injury [66] and optic nerve lesion [67] and is involved in the regenerative growth of Purkinje cell axons in vivo [68] .…”
Section: Cell Adhesion Moleculesmentioning
confidence: 99%
“…With an intact optic nerve, lens puncture still allowed macrophage infiltration into the eye that caused an increase in GAP-43 expression in ganglion cells across the entire retina [52]. GAP-43 and L1 have been shown to act synergistically to promote the regenerative outgrowth of Purkinje cell axons in vivo [104]. Purkinje cells do not express GAP-43 or L1 in adult mammals or regenerate axons into peripheral nerve grafts [104].…”
Section: Gap-43 Neurotrophins Cell Adhesion Molecules Developmentmentioning
confidence: 99%
“…GAP-43 and L1 have been shown to act synergistically to promote the regenerative outgrowth of Purkinje cell axons in vivo [104]. Purkinje cells do not express GAP-43 or L1 in adult mammals or regenerate axons into peripheral nerve grafts [104]. Transgenic mice were generated which expressed either L1, GAP-43, or L1 and GAP-43 [104].…”
Section: Gap-43 Neurotrophins Cell Adhesion Molecules Developmentmentioning
confidence: 99%